Milczące wiersze. Obraz i podmiot na tle ekopoetyki - Stusek, Marta (Studia Europaea Gnesnensia, 2018)
The paper aims to show the ecopoetic potential of minimalist poems, in which the lyrical subject remains out of sight. The text discusses poetic techniques of drawing a bare picture of reality, which have the capacity to enact a novel, non-anthropocentric approach to non-human nature. The author combines interpretive practice with the concept of ecopoetics and literary genology.